Alteration in vital signs and clinical outcome of patients admitted to an emergency unit - Oliveira, Gabriella Novelli (2020)
Objective: to describe the characteristics of the nursing records, including the vital signs, and to compare the patient’s clinical outcome according to the presence of alterations in the vital signs in the emergency setting. Method: a cross-sectional study, with retrospective analysis of patient records of adult individuals admitted in May 2018 in an Emergency Room of São Paulo. The data collected from the nursing records were inserted in the REDCap® system and descriptive and inferential analyses were carried out. Results: of the 194 patient records (54.1% male, mean age of 59.7 years old), the complaints at admission, comorbidities and first care measures carried out in the emergency room were the most written down records. Heart and respiratory rates and blood pressure were the most altered and death-associated vital signs. Conclusion: the clarity and frequency of the nursing records, as well as the correct interpretation of the vital signs, are essential components for the safety of the care provided to the emergency patient.